Peningkatan pH dengan Pemberian Bahan Organik pada Pengelolaan Air Asam Tambang Menggunakan Metode Passive Treatment - Titian Okta Pitaloka; Akhmad Rizalli Saidy; Fadly Hairannoor Yusran (Acta Solum, 2023)
Mining is the process of extracting beneficial minerals from the surface of the earth that have an impact on the formation of acid mine drainage (AMD). One method of passive AMD management is passive treatment. This study used the Nested Factorial Experiment Design method. The types of organic matter used were empty fruit bunch oil palm (EFB) and cow dung, with doses of 0 Mg ha-1 (control), 50 Mg ha-1, 100 Mg ha-1, 150 Mg ha-1 and 200 Mg ha-1. Each treatment was three repeats so that 30 units of experimental units were obtained. The pH value of AMD in the untreated (control) reactor was 3.67. The initial reaction (pH) of AMD (0 days) with EFB application at a dose of 50 – 200 Mg ha-1 ranged from 3.63 – 4.28 and the initial pH of cow dung was 3.84 – 4.13. The reaction (pH) of the 1st to 4th weeks of AMD after adding EFB organic matter at a dose of 50 – 200 Mg ha-1 show a pH range (6.38 – 7.59) and cow manure at a dose of 150 – 200 Mg ha-1 show a pH (6.09 – 7.01). The conclusion are that the application of EFB organic matter on constructed wetland media for 4 weeks had a very real effect on increasing the pH of the AMD dose of 100 – 200 Mg ha-1 while cow dung 150 – 200 Mg ha-1 are the most effective against increasing pH.